Activity and safety of apatinib monotherapy or apatinib combined with chemotherapy for patients with metastatic or unresectable osteosarcoma over the age of 40 years: A retrospective analysis - Gong, Taojun; Huang, Qi; Tang, Fan; Wang, Yitian; Li, Zhuangzhuang; Luo, Yi; Min, Li; Zhou, Yong; Tu, Chongqi (Frontiers in Oncology, 2022)
Background Osteosarcoma commonly develops during childhood and adolescence. Only one-third of osteosarcoma patients have been clinically detected over the age of 40 years, and the survivorship of those patients is quite dismal. Apatinib, a novel multitarget angiogenesis inhibitor, has shown a short-term efficacy in advanced or metastatic osteosarcoma. However, the data for apatinib in the older patients with osteosarcoma are limited. We aim to evaluate the efficacy and safety of apatinib combined with chemotherapy versus apatinib monotherapy in the treatment of patients over 40 years old with metastatic or unresectable osteosarcoma. Methods We retrospectively analyzed the patients with metastatic osteosarcoma who were treated with apatinib monotherapy or apatinib combined with chemotherapy between May 2015 and December 2018 in the Department of Orthopedics at West China Hospital. Apatinib was initially administered with a dose of 500 mg daily, and the dose was adjusted according to toxicity. The objective response rate (ORR), disease control rate (DCR), duration of response (DOR), progression-free survival (PFS), and overall survival (OS) were investigated. The treatment-related adverse events and the safety of apatinib were also documented. Results A total of 45 patients (28 men, 17 women) with metastatic or unresectable osteosarcoma were finally included, and 41 patients received at least one cycle of treatment and were evaluable for efficacy. Of 41 patients, 24 who were intolerant to intensive chemotherapy or have failed standard chemotherapy received apatinib monotherapy, and 17 patients were treated with apatinib plus chemotherapy. The median PFS and median OS were longer in the group treated with apatinib combined with chemotherapy than those of the apatinib monotherapy group (5.6 months vs. 2.6 months; 15.1 months vs. 9.7 months). Moreover, the median DOR was significantly prolonged in the group treated with apatinib combined with chemotherapy compared with that in the monotherapy group. Conclusion Apatinib demonstrated promising activity in patients over 40 years old with metastatic or unresectable osteosarcoma. The combination of apatinib and chemotherapy conferred a durable response compared with apatinib monotherapy, which might be an alternative therapeutic strategy for the management of osteosarcoma in older patients.